Front Cover: Experimental Quantum Embedding for Machine Learning (Adv. Quantum Technol. 8/2022). Issue 8 (12th August 2022) - Gianani, Ilaria; Mastroserio, Ivana; Buffoni, Lorenzo; Bruno, Natalia; Donati, Ludovica; Cimini, Valeria; Barbieri, Marco; Cataliotti, Francesco S.; Caruso, Filippo
Abstract : A quantum embedding protocol embeds classical data into quantum ones living in the more complex Hilbert space where, for instance, they can get split into linearly separable clusters (data classification) or processed for an hybrid quantum machine learning application. The cover image represents the result of this embedding on the Bloch sphere via a parameterized quantum circuit. In article number 2100140 by Filippo Caruso and colleagues, the successful experimental implementations have been realized on two complementary, atomic and photonic, platforms, and compared with a similar analysis running on the cloud‐accessible Rigetti superconducting quantum processor. (Image created by I. Mastroserio)